Xenomelia: A Social Neuroscience View of Altered Bodily Self-Consciousness - Brugger, Peter; Lenggenhager, Bigna; Giummarra, Melita J. (Frontiers in Psychology, 2013)
Xenomelia, the "foreign limb syndrome", is characterized by the non-acceptance of one or more of one’s own extremities and the resulting desire for elective limb amputation or paralysis. Formerly labeled 'body integrity identity disorder' (BIID), the condition was originally considered a psychological or psychiatric disorder, but a brain-centered Zeitgeist and a rapidly growing interest in the neural underpinnings of bodily self-consciousness has shifted the focus towards dysfunctional central nervous system circuits. The present article outlays both mind-based and brain-based views highlighting their shortcomings. We propose that full insight into what should be conceived a “xenomelia spectrum disorder” will require interpretation of individual symptomatology in a social context. A proper social neuroscience of xenomelia respects the functional neuroanatomy of corporeal awareness, but also acknowledges the brain’s plasticity in response to an individual’s history, which is lived against a cultural background. This integrated view of xenomelia will promote the subfield of consciousness research concerned with the unity of body and self.